European industrial policy: A crucial element of strategic autonomy - Sebastian Dullien; Jonathan Hackenbroich (Hans-Böckler-Stiftung, Institut für Makroökonomie und Konjunkturforschung (IMK), 2022)
A sea change in the geopolitical environment and the 'green and the digital revolution' are forcing Europe to rethink its approach to industrial policy. Russia's war in Ukraine has ushered in a new era for Europe's economic diplomacy, supply security, and military spending. The war poses a fundamental challenge, and the EU has also set ambitious goals on decarbonisation and digitalisation. The EU's past approach to industrial policy mostly assumes an absence of great power rivalry, a limited relevance of economies of scale, and benign approaches by other countries to international trade. But other countries are now weaponising economic dependencies and markets for many advanced and emerging technologies when these technologies are found in high concentration and have significant spillover effects within the home country of dominating firms. The EU needs to recalibrate its approach and focus on (the emergence of) key industries and key supplies, as well as provide key infrastructure in Europe. The right balance between selective protectionism and openness to trade and investment needs to be struck. The goal of industrial policy should not be to produce everything at home, but to preserve the capability of production. To this end, Europe should target new products or technologies rather than existing ones, enhance market competition rather than protect actors from it, and help more productive companies rather than unproductive ones. The EU could do this with strategic regulation, FDI screening, public procurement and other tools, all while shielding policies from special interest and inefficiency.
urn:nbn:de:101:1-2022110813461444367142
Keywords: 330; European Policy; Industrial Policy